Analisis Faktor Kesulitan Belajar Siswa dalam Mata Pelajaran Ekonomi Pada Pembelajaran Daring di Masa Pandemi Covid-19 - Riska Amelia Zulfi; Rita Syofyan (Jurnal Ecogen, 2021)
This study aims to confirm and analyze the causative factor of learning difficulties on online learning during Covid-19. The population in the research is 107 students of SMA Negeri 4 Sungai Penuh and the sample is 74 students obtained using accidental sampling technique. The data is collected with questionnaire from 74 respondents who doing online learning during covid-19. The data will be analyzed using descriptive and confirmatory factor analysis. The result of the analysis show that motive factor, school environmental factors, the peer factor, family factor, community factor, study habits factor, motive factor, mass media are the factors that influences the causative of learning difficulties on online learning during Covid-19. From the results of the research analysis, recommended to students, school and families can work together in order online learning to run well.Keywords : learning difficuties, causative factors, online learning, covid-19